LANGUAGE MAINTENANCE OF NIAS LANGUANGE IN GUNUNG SITOLI CITY – NIAS - Hia, Yuniarti (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2025)
This study aims to investigate the language maintenance of Nias Language in GunungSitoli Nias. The maintenance of vernacular has always been a challenging study for investigation. It has its own challenge as it stands among the national language and foreign language. These days vernaculars seem to be facing a threat to be maintenanced in their domains. The hit of English referred as a prestigious language at schools and Indonesian Language as a communication language has signed of a language shift. Nias language as a vernacular is one of the vernaculars that is needed to be preserved which have withstood the cultural strength among the speakers. The older speakers tend to speak Indonesian and only use Nias Language among their generation. The young generation comprehend the Nias Language through their listening during the parents spoken. This circumstance makes Nias Language remains a major concern for Niasnese parents, linguists, educators, language activists and for immigrant families, who need to support and maintain their vernaculars for the next generation.